Recent developments in the assessment of the immune response to malaria, especially as related to vaccination: In vitro inhibition of the growth of Plasmodium falciparum by Aotus serum - Campbell, G. H. (1979)
An in vitro assay for measuring growth and reinvasion inhibition of Plasmodium falciparum was developed from a microculture system. Inhibition of growth was observed after parasites had been incubated with Aotus serum obtained from monkeys that had become immune to malaria after repeated exposure to P. falciparum. Immune Aotus serum (IAS), at concentrations as low as 1.25%, showed a marked inhibitory effect upon parasites cultured in 10% normal human serum (NHS). Growth was also inhibited when 5% of normal Aotus serum (NAS) was added to medium containing 10% of NHS. The inhibitory activity of NAS, but not of IAS, could be removed by lowering serum concentrations below 2.5% or by exposing the serum to 56°C for 30 minutes. Further investigations with relatively synchronous microcultures showed that (3)H-hypoxanthine, a nucleic acid precursor, was incorporated preferentially into the more mature parasites of P. falciparum. Additional studies with the microculture system should elucidate the effects of immune serum on different asexual erythrocyte stages and, in general, facilitate the study of immune effector mechanisms in falciparum malaria.